A rare extensive clinical presentation of calciphylaxis due to primary hyperparathyroidism - A., Mohamad Safwan; Vijayan, K. N.; S., Akash; T., Ashwini; K. P. C., Muhammed Irfan (International Surgery Journal, 2020)
Calciphylaxis is a dreadful condition predominantly seen in chronic kidney disease patients on haemodialysis or following renal transplant. Calciphylaxis occurring in patients with normal kidney function is extremely rare. Here we present 53-year-old women presented with painful, extensive eschar-like skin lesions involving bilateral lower limb of 3 months of duration. She had hypercalcemia, high serum parathyroid hormone (PTH) levels and elevated alkaline phosphatase. Ultrasound neck and sestamibi scan demonstrated left inferior parathyroid adenoma. Lower limb radiographic studies showed subcutaneous calcification. Cutaneous biopsy confirmed calciphylaxis. Cinacalcet to control hypercalcemia, antibiotics and pain control medications were started. Left inferior parathyroidectomy and debridement of gangrenous lesions of lower limbs were performed. Histopathology was consistent with parathyroid adenoma. Lower limb wound started granulating with Vacuum-assisted closure (VAC) dressing and skin graft was planned. Unfortunately, she succumbed 11 weeks from surgery due to proximal myopathy, aspiration pneumonitis, sepsis and multiorgan failure.